(untitled) (Medico Legal Update, 2020)
Background: Women are the main actors in reducing infant mortality. Objective: To develop suitable models of woman’s participation to support government policy reducing infant mortality in Kupang District. Methods: qualitative method was used and 14 informants and 3 triangulations were selected by purposive sampling technique, followed by snowball sampling. Intervewers consists of 5 midwives, 5 cadres, and 3 chiefs of the village. Findings: The degree of women’s participations in this study were low. Forms of participations showed that one Timorese has been given birth at home. Most of the East Timorese informants late reported their pregnancy, gave the porridge sun for babies after 6 months. TIHERO model of woman participation has been created in this study. Recommendation: It is expected that Government to open childbirth education class and model of women participacion must be conduct in terms of reducing neonatal and infant mortality rate.